2017
DOI: 10.1080/14647273.2017.1380317
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about and attitude towards fertility preservation in young female cancer patients: a cross-sectional online survey

Abstract: Recent advances in cancer therapy have resulted in an increased number of long-term cancer survivors. However, because of their treatment, women might be confronted with impaired fertility. The options of fertility preservation (FP) techniques are increasing. The goal of this study was to assess knowledge about, and attitudes towards, fertility preservation in young female cancer patients. A cross-sectional online survey was conducted including 155 former female cancer patients from English and German speaking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 65 publications
2
25
0
1
Order By: Relevance
“…Compared with a sample of women from the USA, no significant differences were found among Portuguese women on the importance of fertility issues after a breast cancer diagnosis. These results are corroborated by other studies,10 11 demonstrating that women value these issues regardless of culture, background or the health system they belong to 8. For some women, fertility concerns are important enough to influence or even change therapeutic decisions 8…”
Section: Introductionsupporting
confidence: 80%
“…Compared with a sample of women from the USA, no significant differences were found among Portuguese women on the importance of fertility issues after a breast cancer diagnosis. These results are corroborated by other studies,10 11 demonstrating that women value these issues regardless of culture, background or the health system they belong to 8. For some women, fertility concerns are important enough to influence or even change therapeutic decisions 8…”
Section: Introductionsupporting
confidence: 80%
“…However, they also found that significantly more patients with gynecological cancer received information compared to those with nongynecological cancer [33]. In contrast, studies conducted in the US and Switzerland found that more than 70% of the participants were informed by their healthcare professionals about fertility impairment after cancer treatment [31,34]. This regional difference in physician counseling may be due to a greater adherence to guidelines in countries like US and Switzerland in comparison to India, Brazil and Iran [32,33].…”
Section: Discussionmentioning
confidence: 96%
“…ASCO and ASRM guidelines recommend that patients with cancer should be given sufficient information about cancer treatment-related infertility and available fertility options [29]. However, studies have shown that physicians and patients have insufficient knowledge about FP [30,31]. Chehin et al [32] assessed patients with cancer for their knowledge and awareness about FP and found that only 34% of the women were aware that cancer therapy could lead to infertility and only 22% were aware of FP options.…”
Section: Discussionmentioning
confidence: 99%
“…9 Se menciona la importancia de proveer información a la paciente con respecto al envejecimiento ovárico fisiológico, el efecto que suponen tratamientos oncológicos y/o inmunosupresores sobre su fertilidad así como los diferentes métodos de preservación de fertilidad actuales, su eficacia, límites y los desafíos relativos a su aplicación. 55,56 Igualmente el médico debe tener una noción general de los fármacos capaces de alterar la fertilidad y conocer su clasificación dependiendo de la toxicidad que ejercen sobre los gametos para poder aconsejar de manera correcta y oportuna a sus pacientes. 57 En la Tabla 1 enumeramos los principales medicamentos gonadotóxicos.…”
Section: Oncofertilidadunclassified